2020
DOI: 10.1002/jbt.22629
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SOX11 in fetal heart tissue, under hyperglycemic environment, mediates cardiomyocytes apoptosis

Abstract: Gestational diabetes mellitus is one of the causes of abnormal embryonic heart development, but the mechanism is still poor. This study investigated the regulatory mechanism and role of SOX11 in congenital heart abnormality in a hyperglycemic environment. Immunohistochemistry, Western blotting, and quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) showed decreased SOX11 protein and messenger RNA (mRNA) levels in the heart tissue of diabetic offspring compared with the control group. A Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Both in vivo and clinical studies have proven that cardiac apoptosis plays a major role in the regressed function of the heart in diabetic conditions, mainly induced and derived from a high glucose level [ 55 , 56 , 57 ]. Caspases are a family of inactive proenzymes that play an important role in apoptosis.…”
Section: Diabetic Cardiomyopathy: Understanding the Cardiac Oxidative Stress Inflammation And Apoptosis-related Pathophysiology And Pathomentioning
confidence: 99%
“…Both in vivo and clinical studies have proven that cardiac apoptosis plays a major role in the regressed function of the heart in diabetic conditions, mainly induced and derived from a high glucose level [ 55 , 56 , 57 ]. Caspases are a family of inactive proenzymes that play an important role in apoptosis.…”
Section: Diabetic Cardiomyopathy: Understanding the Cardiac Oxidative Stress Inflammation And Apoptosis-related Pathophysiology And Pathomentioning
confidence: 99%
“…Moreover, SOX11 is reportedly essential for the pulmonary inflammatory response 40 , and SOX11 knockout mice demonstrated serious developmental defects, including defects related to the heart, spleen generation, skeletal development, and the development of the anterior ophthalmic ganglion 41 . Lastly, Su et al 20 identified that SOX11 overexpression represses apoptosis in cardiomyocytes after hyperglycemia treatment. In our study, SOX11 was upregulated in cardiac fibrosis samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, defective expression of SOX11 caused malformations in various human organs and systems, including the lungs, heart, and skeletal and gastrointestinal systems 19 . A recent study showed that SOX11 downregulation in fetal heart tissue mediated cardiomyocyte apoptosis 20 .…”
Section: Introductionmentioning
confidence: 99%
“…GO analysis showed that SOX11 expression was positively enriched in gene regulatory mechanisms as well as multiple immune response pathways, while SOX11 expression was negatively enriched in the regulation of cell cycle G1/S transition, epidermal cell growth, epidermal cell differentiation and epithelial migration. SOX11 has been reported to affect apoptosis-associated cell survival pathways, TEAD2 transcriptional activity, mitosis and immune-inflammatory responses [ 15 , 48 , 64 ]. It has also been shown that SOX11 may be associated with specific key pathways related to certain developmental processes, including the WNT signaling pathway and the TCF/β-linked protein complex in hepatocellular carcinoma [ 65 ].…”
Section: Discussionmentioning
confidence: 99%